Monitoring wound healing with topically applied optical NanoFlare mRNA nanosensors - Hwang, Jangsun (2023)
An effective wound management strategy needs accurate assessment of wound status throughout the whole healing process. This can be achieved by examining molecular biomarkers including proteins, DNAs, and RNAs. However, existing methods for quantifying these biomarkers such as immunohistochemistry and quantitative polymerase chain reaction are usually laborious, resource-intensive, and disruptive. This article reports the development and utilization of mRNA nanosensors (i.e., NanoFlare) that are topically applied on cutaneous wounds to reveal the healing status through targeted and semi-quantitative examination of the mRNA biomarkers in skin cells. In 2D and 3D in vitro models, the efficacy and efficiency of these nanosensors are demonstrated in revealing the dynamic changes of mRNA biomarkers for different stages of wound development. In mouse models, this platform permits the tracking and identification of wound healing stages and a normal and diabetic wound healing process by wound healing index in real time.